Income Inequality and Poverty in Colombia - Part 2. The Redistributive Impact of Taxes and Transfers - Joumard, Isabelle (OECD Economics Department Working Papers, 2013)
Income inequality in Colombia has declined since the early 2000s but remains very high by international standards. While most of the inequality originates from the labour market, wealth - and thus capital income - is also highly concentrated and the tax and transfer system has little redistributive impact. The tax-to-GDP ratio remains low. Consumption taxes, which tend to be regressive, account for the bulk. The progressivity of income taxes had been undermined by generous tax reliefs, which benefit the well-off most and increase tax avoidance opportunities. The tax system should be reformed to enhance progressivity and raise more revenue which could be used to expand social policies. Cash transfers to households are small and dominated by non-redistributive schemes such as contributory pensions. Education coverage has increased steadily but quality and equity in access at the tertiary level remain important issues. Though significant progress has been made towards universal health coverage, the financing and organisation of the health care system could be improved to raise the quality of care and reduce adverse incentives to remain in the informal sector